Critically Ill Patients With the Middle East Respiratory Syndrome: A Multicenter Retrospective Cohort Study. Issue 10 (October 2017) - Arabi, Yaseen M.; Al-Omari, Awad; Mandourah, Yasser; Al-Hameed, Fahad; Sindi, Anees A.; Alraddadi, Basem; Shalhoub, Sarah; Almotairi, Abdullah; Al Khatib, Kasim; Abdulmomen, Ahmed; Qushmaq, Ismael; Mady, Ahmed; et al.
Abstract : Objectives: To describe patient characteristics, clinical manifestations, disease course including viral replication patterns, and outcomes of critically ill patients with severe acute respiratory infection from the Middle East respiratory syndrome and to compare these features with patients with severe acute respiratory infection due to other etiologies. Design: Retrospective cohort study. Setting: Patients admitted to ICUs in 14 Saudi Arabian hospitals. Patients: Critically ill patients with laboratory-confirmed Middle East respiratory syndrome severe acute respiratory infection ( n = 330) admitted between September 2012 and October 2015 were compared to consecutive critically ill patients with community-acquired severe acute respiratory infection of non–Middle East respiratory syndrome etiology (non–Middle East respiratory syndrome severe acute respiratory infection) ( n = 222). Interventions: None. Measurements and Main Results: Although Middle East respiratory syndrome severe acute respiratory infection patients were younger than those with non–Middle East respiratory syndrome severe acute respiratory infection (median [quartile 1, quartile 3] 58 yr [44, 69] vs 70 [52, 78]; p < 0.001), clinical presentations and comorbidities overlapped substantially. Patients with Middle East respiratory syndrome severe acute respiratory infection had more severe hypoxemic respiratory failure (PaO2 /FIO2 : 106 [66, 160] vs 176 [104, 252]; p < 0.001) and more frequent nonrespiratory organ failure (nonrespiratory Sequential Organ Failure Assessment score: 6 [4, 9] vs 5 [3, 7]; p = 0.002), thus required more frequently invasive mechanical ventilation (85.2% vs 73.0%; p < 0.001), oxygen rescue therapies (extracorporeal membrane oxygenation 5.8% vs 0.9%; p = 0.003), vasopressor support (79.4% vs 55.0%; p < 0.001), and renal replacement therapy (48.8% vs 22.1%; p < 0.001). After adjustment for potential confounding factors, Middle East respiratory syndrome was independently associated with death compared to non–Middle East respiratory syndrome severe acute respiratory infection (adjusted odds ratio, 5.87; 95% CI, 4.02–8.56; p < 0.001). Conclusions: Substantial overlap exists in the clinical presentation and comorbidities among patients with Middle East respiratory syndrome severe acute respiratory infection from other etiologies; therefore, a high index of suspicion combined with diagnostic testing is essential component of severe acute respiratory infection investigation for at-risk patients. The lack of distinguishing clinical features, the need to rely on real-time reverse transcription polymerase chain reaction from respiratory samples, variability in viral shedding duration, lack of effective therapy, and high mortality represent substantial clinical challenges and help guide ongoing clinical research efforts. Abstract : Supplemental Digital Content is available in the text.